Effect of diode low level laser and red light emitting diode irradiation on cell proliferation and osteogenic/odontogenic differentiation of stem cells from the apical papilla - Afsaneh Rahmati; Roshanak Abbasi; Rezvan Najafi; Loghman Rezaei-soufi; Hamed Karkehabadi (BMC, 2022)
Abstract Background This experimental study aimed to assess the effect of irradiation of red light-emitting diode (LED) and Diode low-level laser (LLL) on osteogenic/odontogenic differentiation of stem cells from the apical papilla (SCAPs). Materials and methods SCAPs were isolated from the human tooth root. The experimental groups were subjected to 4 J/cm2 diode low level laser and red LED irradiation in osteogenic medium. The control group did not receive any irradiation. Cell viability/proliferation of SCAPs was assessed by the methyl thiazolyl tetrazolium (MTT) assay on days 1 and 2 (n = 9). Osteogenic differentiation was evaluated by alizarin red staining (ARS) (n = 3), and expression of osteogenic genes by real-time polymerase chain reaction (RT-PCR) (n = 12) on days 1 and 2. SPSS version 18 was used for data evaluation. The Kruskal-Wallis and Mann-Whitney tests were used to compare the groups at each time point. Results The MTT assay showed no significant difference in cell viability/proliferation of SCAPs in the low level laser, red LED, and control groups at 24 or 48 h (P < 0.001). The ARS assessment showed that low level laser and red LED irradiation enhanced osteogenic differentiation of SCAPs. low level laser and red LED irradiation both induced over-expression of osteogenic/dentinogenic genes including alkaline phosphatase (ALP), dentin sialophosphoprotein (DSPP), dentin matrix protein 1 (DMP-1), and bone sialoprotein (BSP) in SCAPs. Up-regulation of genes was significantly greater in low level laser irradiation group than red LED group (P < 0.001). Conclusion Diode low level laser irradiation with 4 J/cm2 energy density and red LED irradiation enhanced osteogenic differentiation of SCAPs without adversely affecting cell viability.